Cannabinoids and monoaminergic system: implications for learning and memory - Zhao, Sha; Gu, Zhao-Liang; Yue, Ya-Nan; Zhang, Xia; Dong, Yuan (Frontiers in Neuroscience, 2024)
Cannabinoids and the endocannabinoid system (ECS) have been intensively studied for their neuroregulatory roles in the central nervous system (CNS), especially in regulating learning and memory. However, many experimental and clinical studies obtained conflicting results indicating a complex network of interaction underlying the regulation of learning and memory by different cannabinoids and the ECS. The ECS influences neuronal synaptic communications, and therefore may exert different regulation via their different impact on other neurotransmitters. The monoaminergic system includes a variety of neurotransmitters, such as dopamine, norepinephrine, and serotonin, which play important roles in regulating mood, cognition, and reward. The interaction among cannabinoids, ECS and the monoaminergic system has drawn particular attention, especially their contributions to learning and memory.In this review, we summarized the current understanding of how cannabinoids, ECS and the monoaminergic system contribute to the process of learning and memory, and discussed the influences of monoaminergic neurotransmission by cannabinoids and ECS during this process.